Predicting Academic Performance in students by an Analytical study on Big Data Machine Learning Techniques - Naren, J.; Vithya,, G.; Reddy, Bharath (International Journal of Psychosocial Rehabilitation, 2024)
Education is the key to solving the majority of world problems. It is important that the education imparted is assimilated by every student who aspires to learn. Classifying slow learners in the early stages so that necessary help can be given to improve their performance is one of the crucial responsibilities for educational institutions. Technology plays an important role in aiding in the process of classifying students. Various techniques have been developed to predict the performance of students accurately for addressing their learning needs and styles. In the present paper, a bird's-eye view of the data mining and machine learning techniques used for predicting student performance is presented.